The Addition of Calcium Carbonate (CaCO3) from Anadara granosa and Glycerol on The Quality of Bioplastic - Ratnawati, Rhenny; Widyastuti, Sri; Evawati, Diana; Susilowati; Diyana, Ulfatud (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Bioplastic material is derived from natural materials that microorganisms can break down producing water and carbon dioxide. With the expansion of chitosan, CaCO3 from Anadara granosa and glycerol, the structure of the materials utilized to create bioplastics from custard squander. The technique utilized was a trial, which started with producing chitosan and CaCO3 from Andara granosa. The production of bioplastics was completed with custard squander composites blended in with Anadara granosa with an organization of 80% : 20% with the expansion of CaCO3 and glycerol. The ratio of CaCO3 and glycerol differed into four creation proportions 0.3 g : 10 mL; 0.3 g : 15 mL; 0.4 g : 10mL; 0.4 g : 15 mL. Tensile strength upsides of tests 1 10.98 MPa. The elongation test values are sample 1 23.79%, sample 2 22.00%, sample 3 19.16%, and sample 4 23.80%. In the after effects of biodegradation tests with soil media, the worth is near sample 2 which can be evaluated by 51.5% with an ideal structure of the proportion of CaCO3 and glycerol 0.3 g : 15 mL.